External Scientific Report - Updated food composition database for nutrient intake - Roe, M.A. (2013)
This report is the final report of the EFSA contract CFT/EFSA/DCM/2011/03. The aim of the project was to provide EFSA with an updated food composition database covering approximately 1750 foods in combination with additional FoodEx2 facet descriptors included in the EFSA FoodEx2 classification system, and to expand the dataset to include harmonised information on the most common composite recipes of European countries and harmonised information on food supplements. Proposals for models of nutrient composition, composite dishes and food supplement databases were developed as well as guidelines for mapping food data in national datasets to EFSA FoodEx2 codes and facet descriptors. A model for data transfer, compatible with the EuroFIR technical annex and CEN Food Data Standard, and the EFSA data structure was developed and tested. Fourteen national food database compiler organisations supplied initial food lists mapped to the EFSA food list. Information on commonly consumed composite dishes was provided by compilers from thirteen countries and information on food supplements was provided by compilers from eight countries. Datasets compatible with EFSA‟s data structure were produced based on the models. In addition, guidelines developed and limitations of the data produced are discussed.